Social Entrepreneurship Challenges: The Implications For Malaysian Government Policies - Raudah,; Wan Yusoff, Wan Fauziah; Awang, Suhaida; Abu Bakar Sidik, Dilaeleyana (Multidisciplinary Applied Research and Innovation, 2020)
This study aims to explore the challenges faced by Malaysia's social entrepreneurship sector to achieve policy implications. This study begins with an overview of the social entrepreneurship sector, the challenges and brief social entrepreneurship in the Malaysian perspective. Data collected from nineteen participants through a semi-structured interview with probes about the experience, knowledge and opinion. To with end, this study summarised that the social organisation has to strategies their organisation to overcome barrier from internal and external factors with the government support. The finding of this contribution research would theoretically have the appropriate framework to enhance government programs and policies in social entrepreneurship. The study also suggests recommending further study of the particular social enterprise that could implement for the future.